(untitled) (Medical Forum Monthly, 2024)
Objective: To compare the skin staples and polypropylene suture for securing mesh in Lichtenstein inguinal hernioplasty in term of post-operative pain. Study Design: Randomized controlled study. Place and Duration of Study: This study was conducted at the Department of Surgery, Nishtar Hospital, Multan from July 2016 to January 2017. Materials and Methods: Total 266 patients of inguinal hernia either male or female and having age 20-60 years were selected. Assessment of post-operative pain was done by using VAS after 24 hours of surgery. Results: Mean age of the patients was 34.37 ± 10.95 years, mean duration of hernia and VAS was 5.52±3.312 years and 4.54±2.811 respectively. Post-operative pain was noted in 39 (29.3%) patients of group A and in 59 (44.4%) patients of group B. Statistically significant (P = 0.02) difference between the frequency of post-operative pain was noted. Conclusion: Results of this study revealed that post-operative pain rate was significantly high in Polypropylene as compared to skin staple group. Significant difference was seen between the male patients of both groups but the difference was insignificant between female patients of both groups. Similarly difference in younger age group as significant but insignificant in older age group for both study groups.